The collection of real property tax for education (R.A. No. 5477) in Mallig, Isabela before and during martial law - Tumaliuan, Desideria Tagulao 1937- (1975)
Insight into the collection of the real property tax for education (R.A. No. 5447) in the municipality of Mallig, before and during the martial law, was provided in this study. The implications of the findings for education were also drawn.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Keywords: State aid to education -- Mallig, Isabela; Real propoerty tax -- Mallig, Isabela